G167 Promoting technology enhanced learning: assessing views and efficiency of mobile phones in clinical practice. (12th March 2018) - Junk, C; Wallace, J; Mallett, P; Thompson, A
Abstract : Aims: Technology-enhanced learning, specifically the use of mobile devices by Healthcare professionals has transformed many aspects of clinical practice. 1 Some healthcare organisations are reluctant to advocate the staff use of mobile phones due to the risks associated with interference of medical equipment, infection control concerns, and reported parental complaints. Mobile devices provide a multitude of benefits for clinical staff including increased access to useful apps such as drug-dose calculators, and other validated point-of-care tools, which are of high educational value and have been shown to support better clinical decision making and improved patient outcomes. 2 Methods: We designed a survey assessing parental and staff perception on the use of mobile phones, using a five point Likert scale. 40 staff and 40 carers participated in the questionnaire. Following this, we designed two clinical scenario's assessing administrator and prescriber performance for healthcare professionals. We assessed length of time to complete task and degree of accuracy. Scenario 1 participants were prohibited from using mobile phones. Subsequently, participants were granted access to mobile phones for assistance in Scenario 2. Results: 38/40 (95%) parents surveyed felt that healthcare professionals should be allowed to use mobile technology in a clinical environment. Similarly, of the 40 staff members surveyed, 39/40 (97%) felt access to mobile phones for clinical reasons was appropriate. For the drug administration scenario (performed by nursing staff), all participants were quicker using mobile phone for assistance. The average length of time was 1 min 22 s quicker. Task accuracy was maintained at 100% with and without mobile phone use. For the prescriber scenario (performed by medics and non-medical prescribers), again all participants were quicker using mobile phone aide, with an average length of 1 min 26 s quicker. Accuracy of 100% was maintained in both cohorts. Conclusion: Despite previous reported parental concern, this survey highlights the strong carer support for healthcare professionals appropriately using mobile phones in clinical areas. Staff members were similarly keen for the use of mobile technology to aid their practice. We have demonstrated an improvement in efficiency of performing clinical tasks with the assistance of mobile phones, ensuring accuracy was maintained. The appropriate use of mobile phones promotes well-informed, safety-conscious, technology-assisted, effective clinical care. References: . Wallace S, Clark M, White J. 'It's on my iPhone': Attitudes to the use of mobile computing devices in medical education, a mixed methods study. BMJ Open2012 August. . Divali P, Camosso-Stefinovic J, Baker R. Use of personal digital assistants in clinical decision making by health care professionals: A systematic review. Health Informatics J2013;19(1):16–28.